Penerapan Model Action Research Dalam Pengembangan Organisasi Dan Perubahan Berencana di SD Negeri 06 Padang Besi, Kota Padang - Dinda Bastari (CV. ITTC INDONESIA, 2025)
This study aims to analyze the application of the Action Research model in organizational development and planned change within several elementary schools in Padang City. Using a qualitative descriptive approach, data were collected through observation and interviews with administrative staff and teachers from seven schools. The findings reveal that the Action Research model—which integrates research with continuous action—has become an effective strategy for improving school management and learning quality. Each school applies the model through cyclic stages: problem identification, joint planning, implementation, evaluation, and reflection. The research shows that collaborative participation between principals, teachers, and administrative staff strengthens the effectiveness of organizational change. Additionally, the adoption of digital administrative systems (such as Dapodik), teacher learning communities, and reflective evaluations have supported sustainable improvement. Thus, the Action Research model is proven to foster planned, data-driven, and participatory organizational development, promoting adaptive, efficient, and high-quality educational environments. The study recommends enhancing collaboration and technological competence among educators to sustain continuous improvement